Analisis Yuridis terhadap Tindak Pidana Penganiayaan yang Mengakibatkan Luka Berat: (Studi Putusan No 297/PID.B/2023/PN JKT.SEL) - Shindy Veronica; Rasji (CV Rewang Rencang, 2024)
Assault can be defined as an intentional act carried out to inflict pain, suffering, or injury upon another person's body. Accordingly, assault is categorized as a criminal offense regulated under criminal law. Based on the provisions of Article 351 paragraph (1) of the Indonesian Penal Code (KUHP), assault that results in serious injury to the victim, whether perpetrated against an individual or certain objects, constitutes an act that must be legally accounted for by the offender. Criminal liability in this context is intended to assess and determine whether a suspect or defendant can be held accountable for the criminal act they have committed, in accordance with applicable legal provisions. The type of research employed in this study is the normative juridical research method. This method focuses on collecting and analyzing legal materials derived from primary sources, such as statutory regulations, legal norms, and principles of law relevant to the topic under discussion. The findings of this research indicate that perpetrators of assault who possess the capacity to be held accountable for their actions can be subjected to penalties commensurate with their conduct. Thus, the imposition of criminal sanctions against perpetrators of assault aims primarily to provide fair and adequate restitution for the rights of victims who have suffered harm as a result of the perpetrator's actions. This includes efforts to ensure justice for the victims, whether in the form of compensation for the damages sustained or as a means of legal protection for the rights violated by the offender.